Pengaruh Variasi Panel Surya dan Solar Charge Controller terhadap Proses Pengisian Daya Baterai Li-Ion - Asrori, Asrori; Nova Ramadhan Dwi Putra (International Forum of Researchers and Lecturers, 2025)
This study analyzes the influence of solar panel type and solar charging technology on the charging performance of lithium-ion batteries. Two types of solar panels, monocrystalline and polycrystalline, were tested alongside two charging technologies: Maximum Power Point Tracking (MPPT) and Pulse Width Modulation (PWM). Experiments measured voltage, current, and charging time parameters, and calculated the State of Charge (SoC) as a performance indicator. The results showed that the combination of monocrystalline panels with MPPT technology achieved the highest charging efficiency and shorter charging times compared to other combinations. These findings indicate that selecting the appropriate panel type and solar charging technology significantly affects lithium-ion battery charging performance, providing valuable considerations for portable solar energy system designs and renewable energy applications.